2007
DOI: 10.1002/ajh.21011
|View full text |Cite
|
Sign up to set email alerts
|

Children with hyperdiploid but not triple trisomy (+4,+10,+17) acute lymphoblastic leukemia have an increased incidence of extramedullary relapse on current therapies: A single institution experience

Abstract: To evaluate the outcome of children with high hyperdiploid acute lymphoblastic leukemia (hHDALL) treated at the author's institution. One hundred thirty-five consecutive children with B-precursor ALL were diagnosed between 1991 and 2002: 38 (28.1%) hHDALL and 97 (71.9%) non-hHDALL. In the hHDALL group, 11/ 38 (28.9%) relapsed at a median interval of 2.8 years (range: 0.8-5.0 years) with 9/11 relapses occurring at the end or after the completion of therapy. Three (27.3%) relapses were isolated hematopoietic (BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…1), it is quite clear that most hypotriploid cases should be included. In practice, the upper limit has been variably defined as 61 (Forestier et al, 2008a), 65 (Moorman et al, 2003;Sharathkumar et al, 2008), and 67 Heerema et al, 2007). In most instances, no reasons are given for choosing a particular cutoff, but in a recent analysis of trisomies and tetrasomies at different modal numbers, Heerema et al (2007) concluded that the chromosomal patterns differed between cases with 51-67 chromosomes and those with >67 chromosomes.…”
Section: Definition Of the High Hyperdiploid Subgroupmentioning
confidence: 99%
“…1), it is quite clear that most hypotriploid cases should be included. In practice, the upper limit has been variably defined as 61 (Forestier et al, 2008a), 65 (Moorman et al, 2003;Sharathkumar et al, 2008), and 67 Heerema et al, 2007). In most instances, no reasons are given for choosing a particular cutoff, but in a recent analysis of trisomies and tetrasomies at different modal numbers, Heerema et al (2007) concluded that the chromosomal patterns differed between cases with 51-67 chromosomes and those with >67 chromosomes.…”
Section: Definition Of the High Hyperdiploid Subgroupmentioning
confidence: 99%
“…However, only a few clinical features have been shown to be associated with decreased EFS within the HeH group, namely age >10 years, male gender, and bone marrow fibrosis. 5,8,9 As regards genetic factors, it has been suggested that some karyotypic patterns and aberrations -low modal chromosome number, lack of certain trisomies, and the presence of various structural changes -confer a more dismal outcome, albeit with conflicting results in different studies. 2,4,5,7,[9][10][11][12][13] The prognostic impact of the "triple trisomies", i.e., concur-…”
Section: Introductionmentioning
confidence: 99%
“…A physical examination demonstrated no remarkable findings. A complete blood count exhibited the following results: WBC of 8.1x10 0%, myelocyte 0%, metamyelocyte 7%, neutrophil 56%, lymphocyte 19%, monocyte 18%), Hb level of 8.6 g/dl, a platelet count of 230x10 9 /l. The bone marrow morphology revealed 4% blasts, granulocyte proliferation with dysplasia and slight dysplasia in the megakaryocytic lineage identified by May-Giemsa staining with Giemsa and May-Grünwald solutions (Muto Pure Chemicals Co., Ltd., Tokyo, Japan), as presented in Fig.…”
Section: Case Reportmentioning
confidence: 94%
“…A 40-year-old female was referred to the Tokyo Medical and Dental University Hospital (Tokyo, Japan), due to an annual medical checkup revealing slight leukocytosis and anemia, with a white blood cell count (WBC) of 12x10 9 /l (myelocyte, 2%; metamyelocyote, 6%) and a hemoglobin (Hb) level of 9.4 g/dl. A physical examination demonstrated no remarkable findings.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation